Humanistic Leadership Based on Uswah Hasanah: An Ethical and Transformative Model for Private University Lecturers - Endang Sarwiningsih Setyawulan; Hasan Hasan (Fakultas Ekonomika dan Bisnis UNTAG Semarang, 2026)
This study aims to develop and test a humanistic leadership model based on Uswah Hasanah as an ethical and transformative paradigm in the context of private universities in Indonesia. The leadership crisis, characterized by an increase in instrumentalist leadership practices and a disregard for the human dimension, necessitates exploring alternative models that place moral exemplarity at the core of leadership. The study employed a mixed-methods sequential explanatory design, integrating a systematic literature review with a survey of private university lecturers selected through purposive sampling. Qualitative data were analyzed using thematic analysis to build a conceptual model, while quantitative data were analyzed using nonparametric statistics (Spearman's Rank Correlation and the Kruskal-Wallis Test) in SPSS 26. The results indicate that the humanistic leadership model based on uswah hasanah consists of four interrelated dimensions: (1) ethics based on human dignity; (2) dialogic and empathetic relationships; (3) moral learning through role models; and (4) sustainable social transformation. Spearman correlation analysis showed a significant positive relationship between all dimensions, indicating strong internal cohesion of the model. The Kruskal-Wallis test revealed significant differences in perceptions of the ethical dimensions and moral learning based on lecturers' tenure, with senior lecturers demonstrating a deeper understanding. Theoretically, this study enriches the discourse on values-based leadership by offering an integrative, contextually grounded synthesis of humanistic management and Islamic ethics. Practically, this model provides an operational framework for leadership development that emphasizes character formation, moral consistency, and organizational culture transformation through role models.